Pengaruh Orientasi Wirausaha dan Kreativitas Terhadap Kinerja Pemasaran Bisnis UMKM Makanan Tradisional Khas Kabupaten Rembang - Setyani, Adinda Dwi Ayu; Nurhidayati, Nurhidayati (Pascasarjana STIE Amkop Makassar, 2024)
UMKM are one sector that the government believes has the potential to contribute to Indonesia's economic growth and prosperity. This study aims to empirically test the influence of business orientation, creativity, and innovative work practices on the marketing of traditional food businesses in Rembang Regency. Primary data in this study from 100 respondents who were UMKM owners engaged in the business sector. The primary data were quantitatively analyzed using Smart PLS software version 3.0. The findings of the study reveal that entrepreneurial orientation significantly influences marketing performance, entrepreneurial orientation significantly affects innovation performance, creativity has a significant impact on marketing performance, creativity significantly affects innovation performance, and innovation performance significantly impacts marketing performance.